1998
DOI: 10.1161/01.str.29.7.1378
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Intima-Media Thickness in the Common Carotid Artery and Atherosclerosis in the Carotid Bifurcation

Abstract: Background and Purpose-An increase in intima-media thickness (IMT) in the common carotid artery (CCA) is commonly used as a marker of atherosclerosis. The purpose of this study was to investigate the relationship between IMT in the CCA and atherosclerosis in the carotid bifurcation. Methods-182 consecutive patients (mean age, 67 years) referred for carotid duplex scanning were included. We measured IMT and classified plaques by means of a high-resolution ultrasound technique. Results-IMT was correlated to age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
61
1
7

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 29 publications
14
61
1
7
Order By: Relevance
“…15) Rosfors, et al have shown that increased carotid intima-media thickness was associated with advanced atherosclerosis at the carotid bifurcation. 21) In some studies, the severity of the stenosis of the carotid atheroma plaques and the number of these plaques were taken into consideration. 18,22) In our study, we defined (n = 27) (n = 31) P Patients without CAS (n = 58)…”
Section: Discussionmentioning
confidence: 99%
“…15) Rosfors, et al have shown that increased carotid intima-media thickness was associated with advanced atherosclerosis at the carotid bifurcation. 21) In some studies, the severity of the stenosis of the carotid atheroma plaques and the number of these plaques were taken into consideration. 18,22) In our study, we defined (n = 27) (n = 31) P Patients without CAS (n = 58)…”
Section: Discussionmentioning
confidence: 99%
“…Increased IMT is in general considered as an important correlate of atherosclerosis. 11,19 The lack of association between the R92Q polymorphism and ischaemic stroke in the GENIC Study may be explained by the lower statistical power of the GENIC Study as compared to the ECTIM Study, especially if the association existed only in a subcategory of stroke. This reduced power would, however, be partially compensated by the higher frequency of the 92Q allele in GENIC than in ECTIM.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the reproducibility of IMT-CCA measurement is also higher than IMT in the bulbs (IMT-BLB) 2,3,16,19), Third, influences of local nonlaminar turbulent blood flow are less in the CCA than in the bifurcation 3). Hence, IMT-CCA measurement might be better for the assessment of general age-related changes in arteries in epidemiological studies 1,2,3) However, the definition of the IMT-CCA in previous studies has not been uniform 20). Some studies defined the IMT-CCA at the maximum point in the IMT 2,3,21) and others defined it as the mean of several fixed points [22][23][24].…”
Section: S-11mentioning
confidence: 99%